How do we know what works? Interview with Prof. Michael Woolcock, Lead Social Scientist at the World Bank - and Evans, Alice (2018)
Dr Alice Evans and leading experts discuss growth, governance, & gender inequalities. Alice is a Lecturer at King's College London, and Faculty Associate at the Harvard Kennedy School.